2016
DOI: 10.1177/1077699016640224
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Oneself Online

Abstract: With a general basis in protection motivation theory, this study builds a three-stage model from online negative privacy experiences to online privacy protection motivation to online privacy protection behaviors. With 2013 survey data ( N = 528), a well-fitting structural equation model was tested, indicating general support for the model’s progression. There was support in only one instance, however, for the mediation role of online privacy protection motivation. In that case, awareness of online information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 58 publications
(128 reference statements)
1
2
0
Order By: Relevance
“…It appears that security concerns and privacy protection behaviour (PPB) did influence the information that registrants were prepared to share. About half of the registrants preferred to share only names and/or email addresses, which was similar to the findings of previous studies (Baek et al, 2014;Chen et al, 2016;Youn and Hall, 2008). Although literature reveals that age (Kezer et al, 2016) and gender (Youn and Hall, 2008) significantly influence PPB, the findings of this study revealed no differences between age and gender groups with respect to PPB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It appears that security concerns and privacy protection behaviour (PPB) did influence the information that registrants were prepared to share. About half of the registrants preferred to share only names and/or email addresses, which was similar to the findings of previous studies (Baek et al, 2014;Chen et al, 2016;Youn and Hall, 2008). Although literature reveals that age (Kezer et al, 2016) and gender (Youn and Hall, 2008) significantly influence PPB, the findings of this study revealed no differences between age and gender groups with respect to PPB.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the respondents (78.1%) preferred to receive registration confirmation and attendance reminders for the online lectures via email as opposed to other methods of communication. This is most likely related to PPB concerns (Baek et al, 2014; Chen et al, 2016). Another explanation is that email is a reliable, cost-effective and real-time communication tool, although a previous study showed that the usage of email as a communication tool has some geographical variations (Tang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The Internet not only benefits individuals but also presents criminals with opportunities. Malicious agencies can collect a large amount of personal data from Web users in the twinkling of eye (Chen et al, 2016; Fenigstein, 1984; Rahman et al, 2020; T. Zhou & Li, 2014).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Second, this study not only extends the Antecedents→Privacy Concerns→Outcomes model to MMHS, but also introduces new constructs, including HIPAA knowledge level and MMH literacy. Third, unlike prior studies that treated privacy data as monotonic [86,125,126], this research for the first time innovatively probes different data types and stages while investigating privacy concerns. The differences in the effects on privacy concerns of different data types and data stages have significant implications for future privacy research.…”
Section: Research Contributionsmentioning
confidence: 99%